Recurrence of an undifferentiated pleomorphic pulmonary artery sarcoma 8 years after initial presentation: a case report - Bourlond, Baudouin; Maurizi, Niccolo; Antiochos, Panagiotis; Skalidis, Ioannis; Auf Der Springe, Katarina; Royer, Claire; Monney, Pierre; Muller, Olivier; Kirsch, Mathias (Frontiers in Cardiovascular Medicine, 2024)
Background Primary cardiac tumors remain exceptionally rare, characterized by a poor prognosis. Among them, sarcomas originating in the pulmonary arteries constitute the most infrequent subgroup within primary cardiac sarcomas. Case summary This report presents the case of a 76-year-old female experiencing a recurrence of an undifferentiated pleomorphic intracardiac pulmonary artery sarcoma located in the right ventricular outflow tract, manifesting 8 years after initial remission. Successful outcomes were attained through a combination of surgical resection, state-of-the-art radiotherapy, and chemotherapy. This comprehensive approach proved essential for optimizing both survival and quality of life. Discussion The unexpectedly prolonged recurrence-free survival observed in this case underscores the effectiveness of the comprehensive multimodal treatment approach outlined in the existing literature. This highlights the pivotal role of a multidisciplinary strategy in addressing primary cardiac sarcomas, particularly those arising in the pulmonary arteries.